Cutaneous adaptive immunity and uraemia: a narrative review - Zibandeh, Noushin; Li, Zehua; Ogg, Graham; Bottomley, Matthew J. (Frontiers in Immunology, 2024)
Chronic kidney disease affects 1 in 10 people globally, with a prevalence twenty times that of cancer. A subset of individuals will progress to end-stage renal disease (ESRD) where renal replacement therapy is required to maintain health. Cutaneous disease, including xerosis and pruritus, are endemic amongst patients with ESRD. In the uraemia-associated immune deficiency of ESRD, impaired circulating immune responses contribute to increased infection risk and poorer vaccination response. Clinical manifestations of dysregulated adaptive immunity within the skin have been well-described and have been posited to play a role in cutaneous features of ESRD. However, our understanding of the mechanisms by which adaptive immunity within the skin is affected by uraemia is relatively limited. We provide an overview of how the cutaneous adaptive immune system is impacted both directly and indirectly by uraemia, highlighting that much work has been extrapolated from the circulating immune system and often has not been directly evaluated in the skin compartment. We identify knowledge gaps which may be addressed by future research. Ultimately, greater understanding of these pathways may facilitate novel therapeutic approaches to ameliorate widespread cutaneous symptomatology in ESRD.